Water supply in the Madrid of Ferdinand VI (1746-1759): civil servants, procedures and documents - Salamanca López, Manuel Joaquín (Revista General de Información y Documentación, 2025)
Abstract. This article analyses the civil servants who were in charge of water supply in one way or another in the Madrid of Ferdinand VI (1746-1759). The historical-administrative and documentary facets are studied, addressing the access to the profession through the files that have been preserved in the Villa de Madrid Archive. In this respect, we have identified the processes that, in one way or another, led to his appointment and the documentation that has resulted from them; the typologies of which have been analysed using diplomatic criteria, in accordance with their internal structure and documentary tradition. To this end, two examples have been selected, embodied in the minor plumbers and the bailiff of the Fountain Council.